Effects of muscle damage induced by eccentric exercise on muscle fatigue - Endoh, T.; Tsuyoshi, N.; Sakamoto, M.; Komiyama, T. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The present study was designed to determine to what extent muscle damage induced by repetitive eccentric exercise with maximal voluntary effort (ECC) affects the time course of central and peripheral fatigue during sustained maximal voluntary contraction (MVC).